Hepatic Carbohydrate Response Element Binding Protein Activation Limits Nonalcoholic Fatty Liver Disease Development in a Mouse Model for Glycogen Storage Disease Type 1a - Lei, Yu (Hepatology, 2020)
BACKGROUND AND AIMS: Glycogen storage disease (GSD) type 1a is an inborn error of metabolism caused by defective glucose‐6‐phosphatase catalytic subunit (G6PC) activity. Patients with GSD 1a exhibit severe hepatomegaly due to glycogen and triglyceride (TG) accumulation in the liver. We have shown that the activity of carbohydrate response element binding protein (ChREBP), a key regulator of glycolysis and de novo lipogenesis, is increased in GSD 1a. In the current study, we assessed the contribution of ChREBP to nonalcoholic fatty liver disease (NAFLD) development in a mouse model for hepatic GSD 1a. APPROACH AND RESULTS: Liver‐specific G6pc–knockout (L‐G6pc (−/−)) mice were treated with adeno‐associated viruses (AAVs) 2 or 8 directed against short hairpin ChREBP to normalize hepatic ChREBP activity to levels observed in wild‐type mice receiving AAV8–scrambled short hairpin RNA (shSCR). Hepatic ChREBP knockdown markedly increased liver weight and hepatocyte size in L‐G6pc (−/−) mice. This was associated with hepatic accumulation of G6P, glycogen, and lipids, whereas the expression of glycolytic and lipogenic genes was reduced. Enzyme activities, flux measurements, hepatic metabolite analysis and very low density lipoprotein (VLDL)‐TG secretion assays revealed that hepatic ChREBP knockdown reduced downstream glycolysis and de novo lipogenesis but also strongly suppressed hepatic VLDL lipidation, hence promoting the storage of “old fat.” Interestingly, enhanced VLDL‐TG secretion in shSCR‐treated L‐G6pc (−/−) mice associated with a ChREBP‐dependent induction of the VLDL lipidation proteins microsomal TG transfer protein and transmembrane 6 superfamily member 2 (TM6SF2), the latter being confirmed by ChIP‐qPCR. CONCLUSIONS: Attenuation of hepatic ChREBP induction in GSD 1a liver aggravates hepatomegaly because of further accumulation of glycogen and lipids as a result of reduced glycolysis and suppressed VLDL‐TG secretion. TM6SF2, critical for VLDL formation, was identified as a ChREBP target in mouse liver. Altogether, our data show that enhanced ChREBP activity limits NAFLD development in GSD 1a by balancing hepatic TG production and secretion.